2013
DOI: 10.1109/toh.2013.49
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Successful Tactile Mapping of Virtual Objects

Abstract: Improving spatial ability of blind and visually impaired people is the main target of orientation and mobility (O&M) programs. In this study, we use a minimalistic mouse-shaped haptic device to show a new approach aimed at evaluating devices providing tactile representations of virtual objects. We consider psychophysical, behavioral, and subjective parameters to clarify under which circumstances mental representations of spaces (cognitive maps) can be efficiently constructed with touch by blindfolded sighted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Using pin arrays seems a promising solution, but prototypes have a too much high price per pin [8]. We have proposed a minimalist tactile mouse and verified that the understanding of simple 2.5D solids is possible [9] in blindfolded individuals. We have also shown that it stimulates visuo-spatial pathways both in sighted and blind subjects [10].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Using pin arrays seems a promising solution, but prototypes have a too much high price per pin [8]. We have proposed a minimalist tactile mouse and verified that the understanding of simple 2.5D solids is possible [9] in blindfolded individuals. We have also shown that it stimulates visuo-spatial pathways both in sighted and blind subjects [10].…”
Section: Introductionmentioning
confidence: 82%
“…Feeling full 3D objects -where the facets opposite to the hand can be touched -would require other more expensive instruments such as the Phantom. However, objects having a curved height profile can be displayed (we discuss vertical resolution of the lever in [9]) and might be easy to perceive. Here we focused on objects for which perception of edges was crucial and almost entirely dependent on subject's strategy and capability of integrating subsequent updown stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, we have shown that touch helps to develop cognitive maps of surroundings in absence of vision (Campus et al, 2012) by eliciting the known phenomenon of sensory substitution (Bach-y-Rita and Kercel, 2003). However, when comparing persons with different degrees of visual disabilities, vision modulates the extent to which tactile information builds up abstract mental models (Brayda et al, 2013, 2015). On the other hand we have also found that brain regions deputed to tacto-spatial processing are similar to those elicited by audio-spatial processing (Leclerc et al, 2005; Campus et al, 2012).…”
Section: Discussionmentioning
confidence: 99%